People's Republic of China-Macao Special Administrative Region : 2016 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2017)
This 2016 Article IV Consultation highlights that the real output for Macao Special Administrative Region (SAR) is expected to contract for a third consecutive year in 2016. However, external demand has begun to recover with gaming revenues posting six consecutive months of positive annual growth. In 2017, a low base will help increase growth above 2 percent despite continued weak domestic demand. Further out, Macao SAR is well-positioned to record sustainable growth in the mid-single digits. In addition to its still highly valuable gaming monopoly within China, Macao SAR is an established tourist destination with significant geographic proximity to Mainland China. Macao SAR is now also investing aggressively in non-gaming tourism and financial services.